Immunocytochemical and Ultrastructural Evidence Supporting That Andes Hantavirus (ANDV) Is Transmitted Person-to-Person Through the Respiratory and/or Salivary Pathways - Pizarro, Enrique; Navarrete, Maritza; Mendez, Carolina; Zaror, Luis; Mansilla, Carlos; Tapia, Mauricio; Carrasco, Cristian; Salazar, Paula; Murua, Roberto; Padula, Paula; Otth, Carola; Rodríguez, Esteban Martin (Frontiers in Microbiology, 2020)
In South America Andes hantavirus (ANDV) is hosted by the rodent Oligoryzomys longicaudatus (also known as pygmy rice rat). In humans, ANDV causes Hantavirus Pulmonary Syndrome (HPS), with a fatality rate of about 40%. Epidemiologic and molecular evidence has shown that ANDV can be transmitted from person to person. Sin Nombre hantavirus, occurring in North America, and ANDV are genetically related, and both cause HPS with similar clinical evolution and mortality rate. However, only ANDV is transmitted from person to person. A recent hantavirus outbreak in a small village in Southern Argentine, with 29 HPS cases and 11 deaths has brought to mind that person-to-person transmission continues to be a public health emergency. The present investigation was aimed to understand how does ANDV actually spread between persons. Tissue samples of lung and salivary glands from infected Oligoryzomys longicaudatus and lethal cases of human HPS were investigated by bright-field immunocytochemistry, multichannel immunofluorescence, and transmission electron microscopy. The findings are consistent with ANDV infection and replication in the lung alveolar epithelium and macrophages, and in the secretory cells of the submandibular salivary glands. In the lung of infected Oligoryzomys longicaudatus and human cases HPS, the bulk of immunoreactive hantavirus antigens was localized in epithelial cells of the alveolar walls and macrophages. The ultrastructural study supports that in the lung of HPS patients the virus replicates in the alveolar epithelial cells with virus particles being discharged into the alveolar lumen. Virus-like particles were seen within vacuoles of the lung macrophages. Considering that these macrophages can reach the conductive segments of the airways, their expectoration becomes a deadly bullet for ANDV transmission. In the submandibular glands of infected rodents and HPS cases, ANDV antigens were in capillary endothelium, the secretory cells and filling the lumen of the excretory pathway. It is proposed that in patients with HPS caused by ANDV the alveolar epithelium and macrophages would be the gate for the airway spreading of the virus, while the salivary glands are a target for virus replication and an exit pathway through saliva.